Guidelines for performing systematic reviews in sports science - Rico-González, Markel; Pino-Ortega, José; Clemente, Filipe; Los Arcos, Asier (Biology of Sport, 2022)
Most of the reviews carried out in sports science have used the general items suggested by Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA). Due to the specific requirements of each knowledge area, several modifications of the PRISMA are necessary to optimize the process of the systematic reviews and, in consequence, the quality of the conclusions provided in this type of study. Therefore, this work aimed to adapt PRISMA to provide specific guidelines to carry out systematic reviews in sports science. The methodology criteria (search strategy, databases, and eligibility) and the results section (flow diagrams and study contents) were adapted based on previous studies, and several new considerations were added to design the new guidelines. We compiled 28 items suggested by sports science researchers and included two new items: (i) population/problem (i.e., age, level, and country) and (ii) the entire training process, which is monitored and compared between groups (e.g., total training load). To maximize the benefit of this document, we encourage people to read it in conjunction with the PRISMA statement. The main differences between PRISMA and the PRISMA adapted to sports science were related to registration, search strategy, flow diagrams, and results. Application of the new guidelines could improve the information provided to readers and make it easier to generalize and compare the results in sports science.